Disinfection byproduct formation during drinking water treatment and distribution: A review of unintended effects of engineering agents and materials. (1st September 2019) - Ding, Shunke; Deng, Yang; Bond, Tom; Fang, Chao; Cao, Zhongqi; Chu, Wenhai
Abstract: Unintended effects of engineering agents and materials on the formation of undesirable disinfection byproducts (DBPs) during drinking water treatment and distribution were comprehensively reviewed. Specially, coagulants, biologically active filtration biofilms, activated carbons, nanomaterials, ion-exchange resins, membrane materials in drinking water treatment and piping materials, deposits and biofilms within drinking water distribution systems were discussed, which may serve as DBP precursors, transform DBPs into more toxic species, and/or catalyze the formation of DBPs. Speciation and quantity of DBPs generated rely heavily on the material characteristics, solution chemistry conditions, and operating factors. For example, quaternary ammonium polymer coagulants can increase concentrations of N -nitrosodimethylamine (NDMA) to above the California notification level (10 ng/L). Meanwhile, the application of strong base ion-exchange resins has been associated with the formation of N -nitrosamines and trichloronitromethane up to concentrations of 400 ng/L and 9.0 μg/L, respectively. Organic compounds leaching from membranes and plastic and rubber pipes can generate high NDMA (180–450 ng/L) and chloral hydrate (∼12.4 μg/L) upon downstream disinfection. Activated carbon and membranes preferentially remove organic precursors over bromide, resulting in a higher proportion of brominated DBPs. Copper corrosion products (CCPs) accelerate the decay of disinfectants and increase the formation of halogenated DBPs. Chlorination of high bromide waters containing CCPs can form bromate at concentrations exceeding regulatory limits. Owing to the aforementioned concern for the drinking water quality, the application of these materials and reagents during drinking water treatment and distribution should be based on the removal of pollutants with consideration for balancing DBP formation during disinfection scenarios. Overall, this review highlights situations in which the use of engineering agents and materials in drinking water treatment and distribution needs balance against deleterious impacts on DBP formation. Graphical abstract: Image 1 Highlights: Unintended effects of drinking water agents and materials on DBP formation were reviewed. Coagulant, ion-exchange resin, nanoparticle or biofilm could serve as the precursors of DBPs. Activated carbon or membrane treatment may transform DBPs to more toxic compounds. Copper corrosion products catalyze the degradation of disinfectants and DBP formation. The unintended effects are mainly associated with the yield of NDMA and brominated DBPs.